2023
DOI: 10.1038/s41598-023-34553-6
|View full text |Cite
|
Sign up to set email alerts
|

Visual tracking of viral infection dynamics reveals the synergistic interactions between cucumber mosaic virus and broad bean wilt virus 2

Abstract: Cucumber mosaic virus (CMV) is one of the most prevalent plant viruses in the world, and causes severe damage to various crops. CMV has been studied as a model RNA virus to better understand viral replication, gene functions, evolution, virion structure, and pathogenicity. However, CMV infection and movement dynamics remain unexplored due to the lack of a stable recombinant virus tagged with a reporter gene. In this study, we generated a CMV infectious cDNA construct tagged with a variant of the flavin-binding… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Table S 3 ). This interplay of differential expression induced by two distinct plant viruses could render the plant even more susceptible state, potentially leading to a more severe infection due to the synergistic effect [ 21 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Table S 3 ). This interplay of differential expression induced by two distinct plant viruses could render the plant even more susceptible state, potentially leading to a more severe infection due to the synergistic effect [ 21 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The visualization of GFP fluorescence signals in living plants was performed using a FOBI fluorescence imaging system (NeoScience, Korea) equipped with a blue light source (excitation at 470 nm) and an emission filter (530 nm short-pass), which effectively eliminates auto-fluorescence signals from chlorophyll 22 . Cellular fluorescence signals in plant leaf tissues were observed using a Leica SP8 laser-scanning confocal microscope (Leica, Germany) equipped with specific laser/filter combinations for GFP (excitation at 488 nm, detection between 510 and 550 nm), aniline blue (excitation at 405 nm, detection between 460 and 500 nm), and chloroplasts (excitation at 568 nm, detection between 580 and 620 nm).…”
Section: Methodsmentioning
confidence: 99%
“…The sequence data were analyzed using ClustalW implemented in MEGA X software 50 . To quantify the accumulation levels of (+)-strand BBWV2 RNAs, RT followed by quantitative PCR (RT-qPCR) was performed using the 2X SYBR Green Real-Time PCR Smart mix (Solgent, Korea) and iCycler iQ5 detection system (Bio-Rad, USA) with the following specific primers: BBWV2-R1-Fw (5′-TCACAGGTTATGCCGCTTGT-3′) and BBWV2-R1-Rv (5′-TCACTCGTCCCAAGCTGTTC-3′) for BBWV2 (+)-strand RNA1 detection; BBWV2-R2-Fw (5′-CCAGAGAAGTGGTTGGTCCC-3′) and BBWV2-R2-Rv (5′-TCCAACAGGTAATGCCCACC-3′) for BBWV2 (+)-strand RNA2 detection 22 . Strand-specific RT-qPCR was performed to quantify the accumulation levels of (-)-strand BBWV2 RNAs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The co-infection rate reached 55.1% in 2016 (Kwon et al 2018 ). A synergic interaction was observed between CMV and BBWV2 in co-infected Nicotiana benthamiana plants using a visual tracking method (Kwon et al 2023 ). This study demonstrated that BBWV2 facilitates the cell-to-cell movement of CMV in upper younger leaves and that the accumulation of BBWV2 increases in plants co-infected with CMV.…”
Section: Introductionmentioning
confidence: 99%